1999
DOI: 10.1021/la9808972
|View full text |Cite
|
Sign up to set email alerts
|

Study of MgO and Pt/MgO Systems by XRD, TPR, and 1H MAS NMR

Abstract: We studied changes in magnesium oxide upon rehydration under operating conditions similar to those used in the subsequent impregnation of a metal salt on its surface. The ensuing transformations were monitored by using the XRD, TPR, and 1H MAS NMR techniques. On the basis of the results, magnesium oxide (periclase phase) is rehydrated to magnesium hydroxide (brucite phase) and dehydrated back to periclase when the calcination temperature is raised to 600 °C. At this point, the transformation occurs simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 45 publications
7
41
0
Order By: Relevance
“…XRD did not identify the presence of MgO (2θ = 37.0, 43.0, 62.4, 74.8 and 78.7° [43,44]) on the calcined zeolite resulting from the NaY zeolite impregnation with the magnesium salt ( Fig. 1).…”
Section: Catalyst Characterisationmentioning
confidence: 97%
“…XRD did not identify the presence of MgO (2θ = 37.0, 43.0, 62.4, 74.8 and 78.7° [43,44]) on the calcined zeolite resulting from the NaY zeolite impregnation with the magnesium salt ( Fig. 1).…”
Section: Catalyst Characterisationmentioning
confidence: 97%
“…The surface area value obtained is small for the three supports. An increase in the surface area is observed in all cases as a result of the thermal treatment of the precursors 15 . A significant change in pore diameter is observed after the thermal treatment at 500 o C in the impregnated calcined MgO as well as in the impregnated agglomerated MgO.…”
Section: Support and Catalyst Characterizationmentioning
confidence: 84%
“…A significant change in pore diameter is observed after the thermal treatment at 500 o C in the impregnated calcined MgO as well as in the impregnated agglomerated MgO. It has been reported that during the thermal treatment of MgO in the range 400-600 o C, there is one point when the pore diameter tends to decrease 15 .…”
Section: Support and Catalyst Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…MgO can be doped with different chemicals to increase its basicity, activity and selectivity for different types of reactions [9]. T. Kanno et al [10] studied the effect of addition of alkali metals to MgO and reported that basicity of MgO increased with the addition of alkali metals.…”
Section: Introductionmentioning
confidence: 99%